THE INFLUENCE OF LEARNING VIDEOS ON LEARNING INDEPENDENCE AND LEARNING MOTIVATION OF PERMATA BUNDA AWALIYAH MIDDLE SCHOOL STUDENTS IN BANDAR LAMPUNG - Indah Rumingsari; Lahmuddin Lubis; Risydah Fadilah (RADJA PUBLIKA, 2024)
This research aims to determine the effect of learning videos on learning independence and learning motivation of Permata Bunda Awaliyah Middle School students in Bandar Lampung. The population of this study was 76 students. Sampling in this study was carried out using a purposive technique, namely taking samples based on certain characteristics, determining the sample by screening during the pre-test, so a sample of 22 students was obtained. This research uses a quasi-experimental method with a ne group pretest posttest design. The measuring instruments used are the learning independence scale and learning motivation scale as well as learning videos. Data analysis used the T test. The results of this study showed that there was no effect of learning videos on student learning independence, with a t coefficient value of -0.181 and a significance value of 0.789 > 0.05, so the hypothesis was rejected. Furthermore, the research results also show that there is no influence of learning videos on student learning motivation, with a t coefficient value of -0.691 and a significance value of 0.493 > 0.05, so the hypothesis is rejected.